Speech perception skills of deaf infants following cochlear implantation: a first report - Houston, Derek M. (2003)
OBJECTIVE: We adapted a behavioral procedure that has been used extensively with normal-hearing (NH) infants, the visual habituation (VH) procedure, to assess deaf infants’ discrimination and attention to speech. METHODS: Twenty-four NH 6-month-olds, 24 NH 9-month-olds, and 16 deaf infants at various ages before and following cochlear implantation (CI) were tested in a sound booth on their caregiver’s lap in front of a TV monitor. During the habituation phase, each infant was presented with a repeating speech sound (e.g. ‘hop hop hop’) paired with a visual display of a checkerboard pattern on half of the trials (‘sound trials’) and only the visual display on the other half (‘silent trials’). When the infant’s looking time decreased and reached a habituation criterion, a test phase began. This consisted of two trials: an ‘old trial’ that was identical to the ‘sound trials’ and a ‘novel trial’ that consisted of a different repeating speech sound (e.g. ‘ahhh’) paired with the same checkerboard pattern. RESULTS: During the habituation phase, NH infants looked significantly longer during the sound trials than during the silent trials. However, deaf infants who had received cochlear implants (CIs) displayed a much weaker preference for the sound trials. On the other hand, both NH infants and deaf infants with CIs attended significantly longer to the visual display during the novel trial than during the old trial, suggesting that they were able to discriminate the speech patterns. Before receiving CIs, deaf infants did not show any preferences. CONCLUSIONS: Taken together, the findings suggest that deaf infants who receive CIs are able to detect and discriminate some speech patterns. However, their overall attention to speech sounds may be less than NH infants’. Attention to speech may impact other aspects of speech perception and spoken language development, such as segmenting words from fluent speech and learning novel words. Implications of the effects of early auditory deprivation and age at CI on speech perception and language development are discussed.